Science and Innovation in Scotland: a Study on the Impact of Enhanced Autonomy - Alessandro Rosiello; Dave Wield; Omid Omidvar; Michele Mastroeni; Joyce Tait (European Regional Science Association (ERSA), 2015)
The Scottish Referendum of September 2014 was the setting for arguments regarding Scotland?s strengths and weaknesses, and projections of what could happen in different scenarios. Areas of debate included those on Scotland?s scientific performance and how to harness innovation to increase its competitiveness in the global economy. It encouraged a high degree of public engagement and prompted the three main political parties in London to promise enhanced devolution of powers and fiscal autonomy if Scotland decided to stay part of the UK. This paper outlines the perception of Scotland as a strong scientific and innovative society, and will outline the images of Scotland as a region and nation both distinct from England in culture and attitude, and as a participant in the knowledge economy. It will summarise the strengths and weaknesses perceived and measured in its science and innovation systems, briefly recount policy initiatives to improve them, and outline the main arguments made by the Scottish Government in 2014 regarding how enhanced autonomy could lead to a more innovative and prosperous Scotland. The science system has been strengthened during the 2000s as devolution brought a set of new and expanded funding streams in conjunction with existing UK-based institutions. There are questions, however, about the relationship between the science base and Scotland?s innovation system, and the lack of coherent policy to address that ?disconnect?. The questions are related to the impact that enhanced autonomy may have on the absorptive and innovation capacities of Scottish business, with a particular focus on the potential impact of increased autonomy on: (i) absorbtive capacity, (ii) the organisations that support Scottish businesses in their innovative activities, R&D, technology transfer, commercialisation and finance, and (iii) on Scotland?s economy in terms of diversity of industry, specialisation and resilience. Beginning with the concept of imagined community, the paper first traces key background elements of the Scottish science system, and the relationship between science and innovation. Then, it details the present situation regarding Scotland?s science base, mapping the institutions that exist to integrate Scottish science policy. It shows that the science system already operates with some autonomy from the rest of the UK. This is followed by an analysis of the tenuous level of connection between science and innovation. The paper will outline the different concerns and opinions of the business and policy communities regarding Scotland?s innovation system, and it will summarise the questions being posed by different stakeholders regarding proposed independence and its possible impact on the Scottish Innovation System. Finally, it presents a summary of the future prospects for science and innovation and an evidenced argument for a less science-led policy led by a focus on new and transformed industrial sectors.
Keywords: O33; O25; 330; Science; Industrial Innovation; Enhanced Autonomy; Scotland